Structured Professional Judgment to Assist the Evaluation and Safety Planning of Suicide Risk: The Risk of Suicide Protocol (RoSP) - Gray, Nicola S.; John, Ann; McKinnon, Aimee; Raybould, Stephanie; Knowles, James; Snowden, Robert J. (Frontiers in Psychiatry, 2021)
Background. The Risk of Suicide Protocol (RoSP) is a structured professional judgment (SPJ) scheme designed in line with NICE guidelines to improve clinicians’ ability to evaluate and manage suicide risk. Aims. This study aimed to evaluate the efficacy of RoSP in two settings: 1) unexpected deaths of people in the community who were known to mental health services; and 2) an inpatient hospital specializing in the assessment and treatment of patients with personality disorder. Method. In Study 1, information from a database of unexpected deaths (N = 68) within an NHS health board was used to complete a RoSP assessment (blind to cause of death) and information from the Coroner’s Court was used to assign people to suicide vs natural causes/accidental death. In Study 2, patients (N = 62) were assessed on the RoSP upon admission to hospital and their self-injurious behaviors were recorded over the first 3 months of admission. Results. (1) Evaluations using RoSP were highly reliable in both samples (ICCs .93 - .98); (2) professional judgment based on the RoSP was predictive of completed suicide in the community sample (AUC = .83) and; 3) was predictive of both suicide attempts (AUC = .81) and all self-injurious behaviors (AUC = .80) for the inpatient sample. Conclusion. RoSP is a reliable and valid instrument for the structured clinical evaluation of suicide risk for use in inpatient psychiatric services and in community mental health services. RoSP’s efficacy is comparable to well-established structured professional judgment instruments designed to predict other risk behavior (e.g. HCR-20 and the prediction of violence). The use of RoSP for the clinical evaluation of suicide risk and safety-planning provides a structure for meeting NICE guidelines for suicide prevention and is now evidence-based.